Sentimental Identity, History and Politics in Daniel Cortezón’s "A vila sulagada" - Sanjurjo Díaz, Santiago (Madrygal. Revista de Estudios Gallegos, 2015)
The novels of Daniel Cortezón, which have not attracted as much critical attention as his theatrical productions, are of contemporary interest as they develop his ideas on identity, history and politics. The purpose of this article is to show, through an analysis of the complex arrangement of the above three concepts, how A vila Sulagada is a metaphor for the historical failure of Galicia.
Keywords: Identity; Sentimentality; History; Politics; Daniel Cortezón; A vila sulagada.